An Arctic ship performance model for sea routes in ice-infested waters. (December 2021) - Ryan, Christopher; Huang, Luofeng; Li, Zhiyuan; Ringsberg, Jonas W.; Thomas, Giles
Abstract: Global warming is creating significant change in the Arctic environment, with widespread reduction in ice extent, thickness and compactness. This has opened numerous shipping routes through the Arctic and provides the opportunity to reduce the distance, time and emissions of voyages. However, for a ship to operate in such polar routes, ice conditions need to be properly accounted for to accurately estimate fuel consumption. To meet this key challenge, this paper presents a ship performance model designed to incorporate a set of ice resistance algorithms alongside the calculation of open-water ship resistance and fuel consumption. In particular, a novel method is proposed to calculate ship resistance in ice-floe fields, other than the traditional level-ice condition. Subsequently, the model has been used to simulate a voyage in the Northern Sea Route and the fuel consumption prediction agrees well with corresponding full-scale measurement data. Overall, the work provides a practical tool for the emerging Arctic shipping industry to carry out fuel analysis and voyage planning.